Religion, politics and ideology in the Third Reich : selected essays - Tal, Uriel (Totalitarian movements and political religions (Series), 2004)
The essays of the late Uriel Tal uncover the dynamics of the secularization of religion, and the sacralization of politics in the Nazi era, to render explicable the deep ideational structure of the history of Nazi Germany and the Holocaust.